ANTHROPOLOGICAL FOUNDATIONS OF PEDAGOGICAL VALEOLOGY (EDUCATION IN THE 21ST CENTURY, 2023)
In the new conditions of the society development, during a pandemic, the value of healthbecomes more relevant. Pedagogical valeology deals with the preservation and strengthening ofhealth. Therefore, it became necessary to study the problems, tasks of pedagogical valeology andeffective ways to solve them. For this aim, we have studied the anthropological foundations of thisscientific field.The purpose of this research was to study the anthropological basis of pedagogical valeology,which, in our opinion, contributes to a deeper understanding of the importance of health in humanlife, to determine the ways of further development of this scientific field. This problem is beingstudied for the first time in Armenia.V. B. Kulikov, Yu. I. Salov and others wrote about the need for anthropological research inpedagogy. J. J. Rousseau, K.D. Ushinsky, and others also refer to this problem. They paid specialattention to the systemic approach in anthropology, which very important in maintaining health.The ideas of P.F. Kapterev, P.F. Lesgaft are also important for pedagogical valeology. P.F.Kapterev believed that every teacher should have anthropological knowledge, know physiology,biology and other sciences in order to contribute to the all-round development of the personality.P.F. Lesgaft created a system of physical exercises, the concept of medical pedagogical control inphysical education, the use of which in pedagogical valeology will undoubtedly preserve andstrengthen the health of students.Analysis of the problems, the content of valeological education from the point of view ofanthropology made it possible to define valeological education as an unlimited process for theformation of integrated knowledge about health.The anthropological approach in pedagogical valeology emphasizes the unity, integrity of alltypes of human health: physical, mental, spiritual.Anthropologization of pedagogical valeology forms the value of health, the systematic natureof pedagogical actions to preserve and strengthen health: valeological support, education,development, etc.197On the basis of the study, it was concluded that for the effective solution of the problems ofpedagogical valeology to strengthen, maintain health, anthropological knowledge is needed, whichwill become a solid theoretical basis for this scientific field.
Keywords: valeology, pedagogical valeology, anthropology, health, healthy lifestyle, valeological education, upbringing.